Physico-chemical characterization of the terbium-161 radioisotope through separation based on cartridge LN resin column from irradiated of enriched Gd2O3 target. (January 2020) - Aziz, A
Abstract: According to WHO, cancer is the second leading cause of death in the world and the seventh cause of death in Indonesia. Currently, cancer sufferers are increasing every year and become a national problem in health. Terbium-161 ( 161 Tb) is a low β − -emitter of radiolanthanide ( Eβ - an average of 0.150 MeV and t1/2 for 6.9 days) that is potential for cancer therapy as an alternative to 177 Lu which has been widely used in nuclear medicine. Physico-chemical characterization of 161 Tb radioisotope in the form of 161 TbCl3 final product solution has been studied including radiochemical purity, radionuclide purity, clarity, acidity (pH), and its stability. Irradiation of the Gd2 O3 enriched target (98.4% 160 Gd isotope enrichment) was carried out at Bandung TRIGA 2000 reactor for ± 3 days. The separation of 161 Tb radionuclide from the Gd/Tb matrix has been done by the extraction chromatography method using two pieces of LN (Eichrom) resin cartridge column. The radiochemical purity of the final product of 161 TbCl3 radioisotope solution was determined using paper chromatography and paper electrophoresis methods. Radionuclide purity of fractions resulted from separation as well as the final products of radioisotope 161 TbCl3 was determined through analysis using a γ -ray spectrometer equipped with a multichannel analyzer (MCA) and HP-Ge detector. The clarity of the solution was determined visually, while the determination of acidity (pH) was carried out using the universal pH indicator paper. In this study, the final product of 161 TbCl3 solution has Physico-chemical characteristics that meet the requirements for nuclear medicine application, namely clear, has a pH of ∼ 1, radiochemical purity of 99.31 ± 0.62%, and radionuclide purity of 99.96 ± 0.03%. The stability of radionuclide purity still meets the requirements (> 99%) for 2 weeks after preparing the final product, but 161 TbCl3 solution with radiochemical purity more than 95% was stable until 3 weeks at room temperature.